Alternative splicing in the dyslexia-associated gene KIAA0319. - Velayos-Baeza, A; Toma, C; da Roza, S; Paracchini, S; Monaco, A (2007)
The KIAA0319 gene in chromosome 6p22 has been strongly associated with developmental dyslexia. In this article we show a wide expression pattern of this gene in human adult brain by Northern blot analysis. We also performed RT-PCR analysis to detect alternative splicing variants in human brain. Most of the detected variants involve alternative splicing of the exons at the 5' and the 3' ends. Two main forms differing in the length of the 5' UTR are detected at approximately the same rate. Two variants (B and C) lacking exon 19, which encodes the transmembrane domain, are the main alternative forms detected among those predicted to encode protein. These two variants could be secreted and might be involved in signaling functions. A similar RT-PCR analysis performed in mouse and rat adult brains showed that only some of the alternative splicing variants are equivalent to those found in the human gene.